Transforming the Ecological Behavior of Santri through the Go Green Program based on the Eco-Pesantren Model - Siti Rozinah; Saiful Bahri; M. Abd. Rahman; Hunaidah Hunaidah; Ahmad Syafiudin (The Institute of Research and Service Community IPMAFA Pati, 2025)
This study addresses the main research question: how the Go Green program at Pesantren Attaqwa Bekasi is implemented and how ecological values, particularly hubbul bi’ah (love and responsibility toward the environment), are internalized in santri behaviour. The study is grounded in the increasing significance of eco-pesantren as an Islamic-based environmental education model, especially following the Indonesian Ministry of Religious Affairs’ ASRI policy, which mandates systematic environmental conservation practices across religious educational institutions. However, it also explores common challenges such as resource limitations, community engagement, and institutional resistance that may affect replication. This research positions eco-pesantren not merely as physical environmental projects but also as pedagogical and managerial frameworks that shape value internalization, habit formation, and institutional support for ecological practices. Using a descriptive qualitative case study, the analysis centres on three core components of the program: greening initiatives, integrated waste management, and the charity-based plastic bottle donation scheme. The findings reveal that the Go Green Program fosters santri behavioural transformation through experiential learning, structured collective habituation, and religious messaging that frames environmental care as a divine mandate. These initiatives not only improve the pesantren’s physical environment but also cultivate ecological character through discipline, responsibility, cooperation, and sustainability awareness. The study further shows that the success of eco-pesantren is determined by governance, community participation, external partnerships, and overcoming implementation barriers. Overall, this research contributes to the development of eco-pesantren models in Indonesia and highlights their potential as replicable forms of sustainability-oriented Islamic education.